Effects of aluminum, nitrate and ammonium on the metabolic nitrogened composition and of carboidrates in Stylosanthes guianensis and S. macrocephala - Amaral, José Augusto Teixeira do; Cordeiro, Antonio Teixeira; Rena, Alemar Braga (Pesquisa Agropecuaria Brasileira, 2000)
The effects of aluminum, nitrate and ammonium interaction, in nutritive solution, on the concentration of nitrogened compound, and of sugar in Stylosanthes guianensis and S. macrocephala, sensitive and tolerant, respectively, both to aluminum and to ammonium were studied under controlled conditions. The ammonium nutrition caused the appearance of toxicity symptoms of ammonium only in the S. guianensis. The ammonium source increased the concentrations of N-soluble, N-ammonium and N-amino acid mainly in the aerial part of the S. guianensis and in the root system of the S. macrocephala, while the total soluble sugar concentration increased in the aerial part of the S. guianensis and decreased in the root system of both species. The aluminum relieved partially the ammonium toxicity in the S. guianensis. When the nitrogen was supplied by the nitric source, the addition of the aluminum to the nutritive solution caused the appearance of symptoms of toxicity only in the S. guianensis. In the S. macrocephala, under the same conditions, an increase of total N, insoluble N, soluble N, nitric N and amino acid N in the aerial part and in the roots ocurred, followed by a decrease in the total soluble sugar concentration and sugar reductor in the roots.